An interpretive structural modelling approach for analysing barriers in total productive maintenance implementation. (1st January 2014) - Singh, Manjinder; Sachdeva, Anish; Bhardwaj, Arvind
To be successful in modern manufacturing environment organisations must be supported by both effective and efficient maintenance programmes. One approach to improving the performance of maintenance activities is to implement and develop a total productive maintenance (TPM) strategy. However, TPM implementation is adversely affected by a few factors, which are known as TPM barriers. The objective of this paper is to develop the relationships among the identified TPM barriers. Further, this paper is also helpful to understand mutual influences of barriers and to identify those barriers which support other barriers (driving barrier) and also those barriers which are most influenced by other barriers (dependent barriers). The interpretive structural modelling (ISM) methodology is used to evolve mutual relationships among these barriers.